In vivo digestibility of morera (Morus alba), with different levels of concentrate in guinea pig (Cavia porcellus) (Revista Sistemas de Producción Agroecológicos, 2020)
Guinea pig (Cavia porcellus) meat is in high demand in Ecuador, Peru and Colombia, mainly in Pasto. It has been shown that their consumption has spread to a large part of the country, there are few studies that involve these animals and much less evaluate the nutritional strategies in their behavior in terms of metabolism and use of nutrients. In the same way, there are no known alternatives, taking into account that this species consumes a large amount of forage, which favors the decrease in meat production costs, avoiding the use of 100% concentrate, since this input has a high cost. In addition, it has a negative influence on the flavor of the meat. The present study was carried out in the municipality of Villavicencio, with an altitude of 465 meters above sea level, an average temperature of 27°C and annual rainfall between 1900 and 3250 millimeters. The guinea pigs were distributed in four treatments with three repetitions and each one with two experimental units, for a total of 24 animals with an average weight of 1027.5 ±19 g distributed in a completely random design, which were housed in cages and subjected to a period of acclimatization of five days, and four days of data collection that was carried out from the fifth day. For each repetition, four samples were taken, which were evaluated in the Animal Nutrition Laboratory of the University of Los Llanos. The diets supplied per day to all the treatments were fresh mulberry (FM) ad libitum, supplemented as follows: T1 with commercial concentrate (CC), 1% of its live weight (LW); T2: CC, 2% of your LW; T3: CC 3% of your LW and T4: FM only. Nutritional analyzes were carried out on the diets and excreta. The variables to evaluate were digestibility coefficients (Cod) of dry matter (DM), protein, fat, non-nitrogenous extract (NNE), crude fiber (CF), % total digestible nutrients (TDN); calculations of: digestible energy (DE) and metabolized energy (ME), Cod: method that assesses the consumption and excretion of nutrients to determine the use in the digestive tract. The study was important in the sense that reference values were estimated for the sector in terms of digestibility of mulberry and commercial concentrate in guinea pigs. It was determined that the diets with the best performance (P
Keywords: shrubby; feeding; Cavia porcellus